Therapeutic Hypothermia in Reanimatology: Past, Present, Future - Usenko, L. V.; Tsarev, A. V. (Problems of Cryobiology and Cryomedicine, 2008)
In the article presented the contemporary notions of mechanisms of therapeutic hypothermia and its application for treatment of the critical states.